Utilization of Information Technology for Tourism Development of Lake Kelimutu, Ende Regency, East Nusa Tenggara With a Virtual Tour Based on Mobile Web - Emanuel Minggu; Bambang Soedijono; Dhani Ariatmanto (Institute of Computer Science (IOCS), 2022)
The development of technology that is increasingly rapid day by day, gives rise to many new innovations from technology. One of the technological development innovations is virtual tours which are starting to be widely used, for example in some applications to introduce a location. However, the use of virtual tour applications as a medium for promoting tourism in Indonesia is still very small. Virtual tour Kelimutu lake tourism in Ende regency, East Nusa Tenggara, was created to be able to visually display information from the natural attractions of lake kelimutu The development methodology used in this study is the Multimedia Development Life Cycle (MDLC) methodology which is a multimedia software design method that emphasizes the 6 stages of multimedia development with this virtual tour users can see the state of 3600 natural lake attractions kelimutu made with immersive photography techniques. By presenting information in the form of a 3600 panoramic image, it makes it easier for users to visually display information from the tourist attraction